Comparative analysis of SIP-libraries. Improvements of JsSIP library - Dubchak, E.V.; Petrash, I.B. (Science-based technologies, 2017)
In this article, are considered the security, accessibility and reliability of the most common SIP-libraries based on JavaScript. It describes of the communication model between a client and a remote host. This article provides a cross-browser comparative analysis of the most common SIP-libraries. The JsSIP library has been considered the most reliable and readily available, thus it is suggested some improvements by considering different types of cyber attacks